Cardioprotective effects of dietary rapamycin on adult female C57BLKS/J‐Leprdb mice. Issue 1 (29th January 2018) - Reifsnyder, Peter C.; Ryzhov, Sergey; Flurkey, Kevin; Anunciado‐Koza, Rea P.; Mills, Ian; Harrison, David E.; Koza, Robert A.
Abstract: Rapamycin (RAPA), an inhibitor of mTORC signaling, has been shown to extend life span in mice and other organisms. Recently, animal and human studies have suggested that inhibition of mTORC signaling can alleviate or prevent the development of cardiomyopathy. In view of this, we used a murine model of type 2 diabetes (T2D), BKS‐ Lepr db, to determine whether RAPA treatment can mitigate the development of T2D‐induced cardiomyopathy in adult mice. Female BKS‐ Lepr db mice fed diet supplemented with RAPA from 11 to 27 weeks of age showed reduced weight gain and significant reductions of fat and lean mass compared with untreated mice. No differences in plasma glucose or insulin levels were observed between groups; however, RAPA‐treated mice were more insulin sensitive ( P < 0.01) than untreated mice. Urine albumin/creatinine ratio was lower in RAPA‐treated mice, suggesting reduced diabetic nephropathy and improved kidney function. Echocardiography showed significantly reduced left ventricular wall thickness in mice treated with RAPA compared with untreated mice ( P = 0.02) that was consistent with reduced heart weight/tibia length ratios, reduced myocyte size and cardiac fibrosis measured by histomorphology, and reduced mRNA expression of Col1a1, a marker for cardiomyopathy. Our results suggest that inhibition of mTORC signaling is a plausible strategy for ameliorating complications of obesity and T2D, including cardiomyopathy.